Determinants of Students’ Entrepreneurial Intention: A Perspective of Tertiary Education in Indonesia - Corry Yohana (Faculty of Economics, State University of Jakarta., 2021)
Entrepreneurial intention measurements are important that should be managed and which can be used to enhance number of entrepreneurs from higher school graduates. This study aims to examine determinant factors affecting students’ entrepreneurial intention from subjective norms, attitudes, self-efficacy, locus of control perspectives and understanding the role of entrepreneurship education. This study adopted a survey with correlation approach to obtain a greater understanding for the phenomenon. The data were collected using purposive method from questionnaire with a five-point Likert scale to voluntary respondents and were analyzed using SPPS application. The findings of the study indicate that the variable of subjective norm, attitude, self-efficacy, locus of control, entrepreneurship education and adversity quotient successfully drive students’ entrepreneurial intention. This study suggests to pay attention these variables in driving students’ entrepreneurial intentions.